Development of Interactive Learning Media with a Wordwall Platform to Improve Students' Mathematical Divergent Thinking Skills - Carissa Aprilia; Netriwati Netriwati; Siska Andriani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical divergent thinking ability is one of the important skills of the 21st century that plays a role in developing students' problem-solving abilities. However, the results of pre-research indicate that students still have difficulty in linking mathematical concepts to real situations and consider mathematics as a difficult subject. This condition indicates the need for innovative, interactive, and interesting learning media to stimulate students' divergent thinking abilities. This study aims to develop a web-based interactive learning media Wordwall that is feasible, interesting, and effective in improving students' mathematical divergent thinking abilities in arithmetic and geometric sequences. This study uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were grade X students of SMA Ma'arif NU 5 Purbolinggo. Data were collected through interviews, questionnaires, and tests with a One Group Pretest-Posttest design. Data analysis was carried out descriptively quantitatively through feasibility, attractiveness, and effectiveness tests with N-Gain calculations. The results of the study showed that the developed media was declared feasible with an assessment of 90.17% from material experts, 97.2% from test experts, and 90.625% from media experts, with a validation of the media's feasibility reaching 96.42%. Student responses reached 92% with a very interesting category, and the N-Gain analysis of the posttest results showed an increase in the average score of students compared to the pretest with an N-Gain value of 0.53 in the small group test and 0.62 in the large group in the